Journalist in the Age of Artificial Intelligence – Can a Chatbot Become an Author in the Media? - Uldrijan, Ivan; Ciboci Perša, Lana; Labaš, Danijel (Anafora, 2024)
The issue of blurring the boundaries between what we can call journalism and what could be called “non-journalism” in the media is not new. It was raised repeatedly with various phenomena that represented considerable professional and ethical challenges for the journalistic profession—from the influence of corporate journalism on the strong trend of tabloidization, through the so-called citizen or participatory journalism, up to the present day in which questions are raised about who is a journalist and what is journalism on the Web which rests on the idea of user co-creation in which anyone can be an author. The question of the future of journalists as authors is particularly serious at a time of increasingly rapid development of various tools driven by artificial intelligence (AI) technology, such as chatbots, for which some predict a stronger application in journalism as well. In the theoretical part of the paper, the identity and the role of the journalist as a professional author in the contemporary digital media environment are considered. The second part of the paper, with the aim of analyzing the views of experts on the future of the journalism profession, presents the results of research conducted using the method of semi-structured in-depth interviews with university professors who educate future journalists at five Croatian universities and teach them journalistic genres and media reporting. The views of university professors on artificial intelligence are investigated and can artificial intelligence replace the journalist as the author of media content, will artificial intelligence lead to the "death" of the journalist as author, and how, in accordance with the development of artificial intelligence and technology in general, the journalism profession will develop in Croatia.